Formação de professores de matemática da educação superior e as tecnologias digitais: aspectos do conhecimento revelados no contexto de uma comunidade de prática online - Richit, Andriceli [UNESP] (2015)
The formation of the Higher Education Professor is discussed within the continuum perspective. Current research involved Math Professors in Brazil and abroad within a formation context and aimed at evidencing and understanding the pedagogical, technological, mathematical, cultural and social aspects of Math Professors within the context of an Online Practice Community. Current research was foregrounded by the question: Which aspects of knowledge emerge in the case of a Higher Education Math professor of an Online Practice Community? Discussion occurs within the qualitative perspective of research, whilst data are retrieved from an online extension course (Modules I, II and III) using Moodle Platform as a base for formation practice developed by synchronic and a-synchronic tools. In the extension course, the capacity of Digital Technologies was discussed within an approach for the concepts of Higher Education Mathematics, specifically Differential and Integral Calculus, Analytic Geometry and Linear Algebra. Further, the manner professors involved developed exploratory and investigative activities related to the disciplines above with the GeoGebra software. Data constituted by elements of Content Analysis, which were related to Chats, Forums, Reviews, Reflexive Memoirs, Final Lesson Plan, Admission Cards, Questionnaire and Course Assessment Card, were analyzed. Four categories developed from data analysis: (1) theoretical-methodological aspects of knowledge of the Higher Education Math Professor within the context of ICTs; (2) didactic-pedagogical, social and cultural aspects of ICTs; (3) epistemological aspects of mathematical concepts; and (4) cultural and political-pedagogical aspects of Math courses. Categories were analyzed by the theories of Practice Communities, TPACK and the Formation of Higher Education professors, and indicate understanding on the investigated object. Current investigation enhanced the capacity of Online Practice ...